Christianity and Culture: A Study of the Encounter of Christianity and Culture in the Development of Church History in Tanah Kisar - Maahury, Yane Rosmawati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to reconstruct the historical and theological process of Gospel dissemination and the interaction between Christianity and local culture in Tanah Kisar. The research uses a historical method combined with social and theological approaches. Data were collected through literature review, archival research, and in-depth interviews with local traditional leaders, religious figures, and youth. The analysis involved source criticism and data interpretation, which were then compiled into a descriptive-analytical historiography. The findings reveal that the spread of the Gospel in Kisar occurred through five main historical periods, beginning with the Portuguese Catholic mission and evolving into the growth of the Protestant Church of Maluku under local leadership. The spread of Christianity was deeply influenced by colonial socio-political dynamics, often resulting in nominal Christian communities with limited spiritual transformation. The study also highlights that local culture, particularly the indigenous language, plays a vital role in evangelism. The church’s tendency to detach from local culture has hindered the process of inculturation. Therefore, revitalizing local culture through contextual approaches is seen as essential to strengthen the presence of an authentic Christian faith within the Kisar community.